2018
DOI: 10.1089/bfm.2018.0002
|View full text |Cite
|
Sign up to set email alerts
|

Serratia marcescensColonization Causing Pink Breast Milk and Pink Diapers: A Case Report and Literature Review

Abstract: Providers evaluating mother-infant dyads with S. marcescens colonization causing pink milk or pink infant soiled diapers should assess for manifestations of systemic infection. In the absence of evidence of clinical infection, expectant management is appropriate and continued breastfeeding can be supported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
7
0
2
Order By: Relevance
“…Previous studies have demonstrated that color of HBM may vary physiologically, in relation to diet, nutritional supplements, infections and medications, from pink to orange, red and green (Ayuzo del Valle and Treviño Salinas, 2014;Jones et al, 2014;Naor et al, 2019;Quinn et al, 2018;Yazgan et al, 2012). The black color of HBM is reported only during minocycline treatment (Basler and Lynch, 1985;Hunt et al, 1996;Lawrence, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that color of HBM may vary physiologically, in relation to diet, nutritional supplements, infections and medications, from pink to orange, red and green (Ayuzo del Valle and Treviño Salinas, 2014;Jones et al, 2014;Naor et al, 2019;Quinn et al, 2018;Yazgan et al, 2012). The black color of HBM is reported only during minocycline treatment (Basler and Lynch, 1985;Hunt et al, 1996;Lawrence, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…HBM can appear pink, red and orange with fruit drinks or green with green color beverages, green vegetables, vitamins or mineral supplements in diet (Yazgan et al, 2012) or intake of blue-green algae (Naor et al, 2019). However, the color of HBM may change for different reasons, as pink color is described in colonization of Serratia marcescens (Ayuzo del Valle and Treviño Salinas, 2014;Jones et al, 2014;Quinn et al, 2018). Moreover, green color is reported after administration of propofol (Birkholz et al, 2009;Rainone et al, 2018).…”
Section: Microbiological Analysismentioning
confidence: 99%
“…It is widespread in farm environments (water, bedding material, bulk tank milk, teat dip, etc.) [ 24 ] and some strains can cause opportunistic infections, including mastitis in both women and dairy cows [ 25 , 26 ]. A preliminary screening for S. marcescens in milk from our region using a chromogenic agar detected about 11% of all members of Enterobacteriaceae present to belong to this species.…”
Section: Discussionmentioning
confidence: 99%
“…[53] Pseudomonas stutzeri (MW148779) [138] Staphylococcus petrasii (MW148788) [163] Aerococcus viridans (MW148771) [164] Serratia marcescens (MW148780) [165] Staphylococcus saprophyticus (MW148789) [166] Bacillus licheniformis (MW148772) [167] Staphylococcus cohnii (MW148782) [168] Staphylococcus simulans (MW148790) [169] Brevibacterium casei (MW148773) [170] Staphylococcus epidermidis (MW148783) [171] Staphylococcus succinus (MW148791) [172] Enterobacter hormaechei (MW148794) [173] Staphylococcus haemolyticus (MW148784) [174] Staphylococcus succinus subsp. casei (MW148792) [172] Paenibacillus glucanolyticus (MW148774) [175] Staphylococcus hominis subsp novobiosepticus (MW148785) [145] Staphylococcus warneri (MW148793) [176] Alternaria spp.…”
Section: Plos Onementioning
confidence: 99%